2017
DOI: 10.4172/2573-4555.1000239
|View full text |Cite
|
Sign up to set email alerts
|

New Approaches in Traditional and Complementary Alternative Medicine Practices: Auricularia auricula and Trametes versicolor

Abstract: Several mushroom species are consumed by collecting from the nature or in cultured form for their nutritional and medical characteristics. The objective of the present study is to determine antioxidant activities, DNA-protective activities, total antioxidant status (TAS), total oxidant status (TOS), oxidative stress indices (OSI) and Fe, Mg, Zn, Cu, Na and Ca content in Auricularia auricula (L.) Underw. and Trametes versicolor (L.) Lloyd mushroom species. Mushroom ethanol extracts were obtained and antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 27 publications
0
28
2
Order By: Relevance
“…It is also known that mushrooms have strong antioxidant capacity in addition to their nutritional properties. Furthermore, mushrooms were reported to possess anticarcinogen, antimicrobial, DNA protective, anti-inflammatory and antiallergic effects in addition to their antioxidant properties (Park et al 2014, Akgül et al, 2016Lima et al 2016, Taofiq et al 2016, Yılmaz et al 2016, Sevindik et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that mushrooms have strong antioxidant capacity in addition to their nutritional properties. Furthermore, mushrooms were reported to possess anticarcinogen, antimicrobial, DNA protective, anti-inflammatory and antiallergic effects in addition to their antioxidant properties (Park et al 2014, Akgül et al, 2016Lima et al 2016, Taofiq et al 2016, Yılmaz et al 2016, Sevindik et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…24 It was reported that the TAS, TOS and OSI values for Auricularia auricula and Trametes versicolor mushrooms were 1.010 and 0.820, 23.910 and 17.760, and 2.367 and 2.166, respectively. 25 TAS value of Lepiota cristata was 2.210, TOS value was 24.357 and OSI value was 1.103. 26 In the present study, it was determined that the TAS value of P. album, a myxomycete species, was lower when compared to C. cylindracea and L. cristata mushrooms as determined in the above-mentioned studies.…”
Section: Tas Tos and Osimentioning
confidence: 89%
“…16 In previous studies, it was determined that the TAS values of Auricularia auricula and Trametes versicolor were 1.010 and 0.820, TOS values were 23.910 and 17.760, and OSI values were 2.367 and 2.166, respectively. 17 In other studies, the TAS value of Pleurotus eryngii was reported as 1.93 and the TAS value of Auricularia polytricha was reported as 0.93. 18,19 It was found in the present study that the antioxidant potential of L. cristata was higher when compared to previous studies conducted on A. auricula, T. versicolor, P. eryngii and A. polytricha.…”
Section: Tas Tos and Osimentioning
confidence: 89%